The Representation of Family Diversity in The Family Book: A Verbal and Visual Analysis - Santosa, Jesica; Sukyadi, Didi; Hermawan, Budi (Journal of Contemporary Social Sciences and Humanities, 2025)
Picturebooks are effective media to raise children’s awareness of various social problems, including family diversity. This study aims to investigate how family diversity is represented verbally and visually in a picturebook entitled The Family Book and elaborate on the signification of the representation. This descriptive qualitative study focuses on finding the ideational meaning by identifying the type of processes used in the clauses and images of the picturebook and the intersemiotic relation between them. The data were analyzed by employing Halliday’s transitivity system, Kress and Leeuwen’s visual grammar, and Royce’s intersemiotic complementarity. The findings showed that for the verbal representation, the most dominant process used in the picturebook is a relational process that is used to identify something or assign a quality. For the visual representation, the predominant process used in the images is a symbolic attributive process. Through the relational and symbolical processes, the diverse identities and characteristics of families are presented and implicitly can determine the types of those families. Additionally, the intersemiotic analysis has found that the working together of the verbal and visual modes in the picturebook have created repetitions and meronymies. These results imply that family diversity in The Family Book is represented as normality. Family diversity as a normal thing is attempted to be explained to the readers not only to enhance their understanding of family but also to influence them to accept the variation of families in society.